2023
DOI: 10.3390/cancers15082212
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Networks in Renal Cell Carcinoma

Abstract: Cancer-associated inflammation has been established as a hallmark feature of almost all solid cancers. Tumor-extrinsic and intrinsic signaling pathways regulate the process of cancer-associated inflammation. Tumor-extrinsic inflammation is triggered by many factors, including infection, obesity, autoimmune disorders, and exposure to toxic and radioactive substances. Intrinsic inflammation can be induced by genomic mutation, genome instability and epigenetic remodeling in cancer cells that promote immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 322 publications
0
8
0
Order By: Relevance
“…Enhanced IL-6-JAK-STAT3 in conjunction with IFN ␣ and IFN ␥ signaling is known to impair cytotoxic T-cell activation resulting in a diminished response to ICIs in clear cell renal cell carcinoma [32]. Gene expression analyses have reported the overexpression of inflammatory and immunerelated signatures among patients who respond to immunotherapy or immunotherapy-containing regimens across different cancers [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced IL-6-JAK-STAT3 in conjunction with IFN ␣ and IFN ␥ signaling is known to impair cytotoxic T-cell activation resulting in a diminished response to ICIs in clear cell renal cell carcinoma [32]. Gene expression analyses have reported the overexpression of inflammatory and immunerelated signatures among patients who respond to immunotherapy or immunotherapy-containing regimens across different cancers [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…This innovative nanoplatform not only demonstrated significant efficacy against tumors but also activated the innate immune system by activating NK cells via the cGAS-STING pathway [127]. This pathway is well known for its role in detecting cytoplasmic DNA and initiating immunological responses [128]. Thus, improving the therapeutic effect of radiation may be achieved by the strategic incorporation of metformin, an immunomodulatory medication that is often used to treat diabetes, into a MnO 2 -based…”
Section: Immunotherapy For Cancermentioning
confidence: 99%
“…Indeed, it has been shown that during the development of RCC, NF-kB pathways are implicated in abnormal inflammatory responses, thereby contributing to the progression of the disease. Loss of the von Hippel Lindau (VHL) tumor suppressor gene, a typical mutation found in most RCC patients that will be discussed below, seems to promote the pathological roles of NF-κB [ 29 ].…”
Section: Immune Checkpointsmentioning
confidence: 99%
“…It has been demonstrated that, in ccRCC, this condition can induce the stabilization of hypoxia-inducible factors-αs (HIF1α and 2α), which in turn can promote metabolic reprogramming, angiogenesis, and epithelial–mesenchymal transition (EMT) associated with the downregulation of tight junction protein (occludin, claudin-1, and E-cadherin) expression and apical–basal polarity loss. The combination of these factors subsequently contributes to the growth and spread of the most common RCC subtype [ 29 , 63 , 65 ].…”
Section: Role Of the Von Hippel Lindau (Vhl) Tumor Suppressor Genementioning
confidence: 99%
See 1 more Smart Citation